Passchendaele - Warner, Philip, 1914-2000. (Barnsley : Pen & Sword Military Classics, 2005)
Nearly ninety years ago, on 31st July 1917, the small Belgian village of Passchendaele became the focus for one of the most gruelling, bloody and bizarre battles of World War 1. By 6th November, when Passchendaele village and the ridge were captured, over half a million British, French, Canadians, Australians, New Zealanders and Germans had become casualties. Philip Warner, the noted historian of twentieth-century warfare and the author of over fifty books on military history, many published by Pen & Sword, has skilfully brought together all the elements of this horrific campaign - the historical background, personal accounts, strategies and tactics, the personalities and the political manoeuvres. He investigates the issues which had a crucial effect on the course of the battle, including the mutinous state of the French army, the bombardment which destroyed the drainage system, Field Marshal Sir Douglas Haig's determination to continue operations despite the appalling weather and ground conditions, and the stormy relationship between Haig and Lloyd George. However, it is the determined fighting ability and the bravery of the allied soldiers, rather than the tactical plans of the commanders, that dominate this detailed and totally absorbing account of the harrowing four-month campaign called the Battle of Passchendaele. Passchendaele is a masterly and timely analysis of one of the most important battles in history.
Intro -- Half Title -- Title Page -- Copyright -- Contents -- Acknowledgements -- List of Illustrations -- 1 It Must Come to a Fight -- 2 The Cockpit of Europe -- 3 The Preliminary Rounds -- 4 The Mines at Messines -- 5 Everywhere Successful -- 6 Did We Really Send Men to Fight in This? -- 7 See You Again in Hell -- 8 The Difficulties Were Greatly Underestimated -- 9 The Focus of a Spider's Web -- 10 The Supporters -- 11 The Other Side of the Hill -- 12 The View from the Trenches -- 13 Hindsight -- 14 Visiting the Battlefield Today -- Select Bibliography -- Index
Originally published: London: Sidgwick & Jackson, 1987.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Ypres, 3rd Battle of, Ieper, Belgium, 1917.; 3e bataille d'Ypres, Ypres, Belgique, 1917.; HISTORY -- Europe -- Western; Belgium -- Ieper; 1917